Improvement of Decision Making Grid Model for Maintenance Management in Small and Medium Industries - Tahir, Zulkifli; M.A., Burhanuddin; A.R., Ahmad; Halawani, Sami (IEEE, 2009)
Small and Medium Industries (SMIs) generate significant contribution in the economic growth in developing countries. To achieve the standard expected product from customers, SMIs must produce marketable product in term of quality, quantity and prices. This requires the investment in technology for supporting daily operation and maintenance management. In previous research, maintenance decision support system has been developed using decision making grid (DMG) model to solve the problem. In this study, the researches apply tri-quadrant technique to cluster the DMG. This study focuses on the effect from the improvement of DMG model in categorizing low, medium and high criterion for the real production floor in SMIs. The result shows not only the reduction of cost and machines downtime but also better reliability on daily maintenance operation.